Respon Pengusaha Kena Pajak Terhadap Pengampunan Pajak Yang Ke-2 (Pendekatan Fenomenologi Kota Kupang) - Danny Wibowo (Department of Management - Institut Shanti Bhuana, 2023)
One of the government's efforts to increase state revenue from taxes is to hold a Voluntary Disclosure Program. This research focuses on the response of entrepreneurs to PKP status in Kupang City, NTT. Taxpayers, in this case, Taxable Entrepreneurs (PKP), know and welcome the Voluntary Disclosure Program (PPS) or volume II tax amnesty. The research was conducted using a qualitative research method where researchers visited taxpayer shops centred in Kupang, NTT, to see the participation and response of the community to the PPS program. The entrepreneurs gave different but quite positive responses to the implementation of the PPS program. They took advantage of this program to avoid administrative sanctions that they would face if there was a tax audit to be conducted on their business and used this opportunity to further develop their business. Of the many responses from entrepreneurs, several entrepreneurs were of the opinion that the implementation of the PPS program could be better for entrepreneurs, especially those with taxable status in small areas such as their towns. They believe the government is only trying to take advantage of their wealth reporting. Therefore, they should make the best use of this program, so they do not feel disadvantaged.